Determinación de colinesterasa sérica, en trabajadores agrícolas, expuestos a plaguicidas, del distrito de san josé, provincia de virú, departamento de la libertad - junio 2010” - Castillo Vásquez, Pedro Enrique (2010)
This study was made with the purpose of determining serum cholinesterase levels in workers exposed to organophosphates. Serum samples were extracted to 100 farmers in the district of San José de Viru, being processed for detection of the enzyme. The results were expressed as age and working time; found concentrations below 5500 U/ L in 56% of the samples. However is not a direct relationship between working time and the serum cholinesterase level, not between age and decreased levels of the enzyme determined.